Evaluation and Selection of the Inhaler Device for Treprostinil Palmitil Inhalation Powder - Gauani, Helena; Baker, Thomas; Li, Zhili; Malinin, Vladimir S.; Perkins, Walter; Sullivan, Eugene; Cipolla, David (Frontiers in Drug Delivery, 2022)
Treprostinil palmitil (TP) is a prodrug of treprostinil that has been formulated as an inhaled powder, termed TPIP, for evaluation in patients with pulmonary arterial hypertension. In these characterization studies we investigated the aerosol performance of TPIP in response to changes in capsule fill, device resistance, and inspiratory flow rate to enable selection of an inhaler for clinical use. Capsules containing 8, 16 or 32 mg of TPIP (80, 160, or 320 µg TP, respectively) were evaluated using four commercially-available, breath-actuated RS01 devices (Plastiape, S.p.A., Osnago, Italy) with low, medium, high or ultra-high inspiratory resistances, creating twelve different capsule and device configurations for evaluation. Aerosol characterization was performed using the next generation impactor at compendial conditions of 23°C and 35% relative humidity and a flow rate corresponding to a 4 kPa pressure drop. The aerosol mass median aerodynamic diameter, geometric standard deviation, fine particle fraction, emitted dose and fine particle dose (FPD) were calculated from the in vitro impactor data. The TP emitted dose at 4 kPa exceeded 75% for all twelve capsule and device configurations. The FPD, an estimate of the respirable dose, varied between 61.0 to 70.6% of the loaded TP dose for all four devices with the 8 and 16 mg TPIP capsule dose. For the 32 mg TPIP capsule dose, the FPD remained above 61.0% for the high and ultra-high resistance devices but decreased to 48.5 and 52.6% for the low and medium resistance devices, respectively. Based on this initial data, the high resistance device was selected for additional characterization studies at 40 and 80 L/min corresponding to pressure drops of 1.4 and 5.4 kPa. The FPD was relatively insensitive to changes in flow rate, providing an expectation of a consistent total lung dose of TP under scenarios simulating variability in how the device is used. Based on these findings, the high resistance device was chosen for further development in human clinical trials.